THE JUNIOR HIGH SCHOOL ENGLISH TEACHERS’ FULFILLMENT OF THE FOUR COMPETENCIES - Febriana, Evi; Faridi, Abdurrachman (Universitas Negeri Semarang, 2016)
This thesis is a study of how the English teachers fulfill the four competencies as stated in the regulation of education minister number 16 year 2007. The study used qualitative method in which purposive sampling technique was employed. Fifteen English teachers from some private and state schools were chosen as the sample of this study. The data of teachers' competence was obtained from interviews and classroom observations. Based on the analysis, the teachers’ fulfillment in pedagogical, professional, personal and social competencies had different results. Based on the teachers’ perceptions, the English teachers’ fulfillment in pedagogical competence was good while the students assumed that the teachers’ fulfillment was fair. Then, concerning professional competence, based on the teachers’ perception, the fulfillment was fair but the students agreed that the fulfillment was fair. In terms of personal and social competence, the teachers agreed that their fulfillment was excellent but the students assumed that the fulfillment was good.